Histopathological study of cutaneous granulomas (Journal of Pathology of Nepal, 2019)
Background: Cutaneous granulomas comprise a wide spectrum of diseases that are frequently encountered. Since clinical assessment alone is insufficient in most of the cases, skin biopsies are a basic requisite in evaluating these lesions. Histopathological examination, although helpful in deciding the nature of granulomas and etiology in most of the cases, maybe noncontributory in some cases, thus requiring further ancillary tests such as microbial culture, polymerase chain reaction.Materials and Methods: This prospective cross sectional study enrolled 109 cases of skin biopsies after histopathological confirmation of granulomatous lesions. The specimens were received at the Department of Pathology from 14th April 2017 to 13th April 2018.Results: Out of 650 skin biopsies, 109 cases (16.8%) were diagnosed as granulomatous lesions on histology. Male predilection was noted and age group of 31 to 40 years was the commonest affected. Upper extremities were more commonly involved. Leprosy was the commonest etiological agent and tuberculoid granulomas were the commonest type based on their histology.Conclusions: Leprosy was the most common cause of cutaneous granuloma followed by Tuberculosis, fungal infection and foreign body reaction. Among the cases of leprosy, borderline tuberculoid leprosy and tuberculoid leprosy were the commonest subtype.